Graph Transformation 9th International Conference, ICGT 2016, in Memory of Hartmut Ehrig, Held as Part of STAF 2016, Vienna, Austria, July 5-6, 2016, Proceedings - Echahed, Rachid; Minas, Mark (Theoretical Computer Science and General Issues, 2016)
This book constitutes the refereed proceedings of the 9th International Conference on Graph Transformation, ICGT 2016, held as part of STAF 2016, in Vienna, Austria, in July 2016. The 14 papers presented in this were carefully reviewed and selected from 33 submissions. They were organized in topical sections named: foundations, tools and algorithms, queries, and applications. The book also contains one keynote paper in full paper length. The book is dedicated to Hartmut Ehrig, one of the fathers and most productive members of the Graph Transformation community, who passed away in 2016. An obituary is included in the front matter of the volume. .